NARRATIVE REVIEW: PERAN ANALISIS BIOMEKANIK GAYA BERJALAN DAN LATIHAN PENGUATAN DALAM PEMULIHAN PLANTAR FASCIITIS - Rakhman, Amalia; Meiza Anniza; Arifa Zulfatunnisa (Indonesian Journal of Physiotherapy, 2025)
Background: Plantar fasciitis is the one of musculoskeletal disorders that causes heel pain due to repetitive stress, leading to inflammation of the plantar fascia. Effective rehabilitation is essential for recovery from this condition. Gait analysis in plantar fasciitis cases is an intriguing aspect to be studied using biomechanical principles. Additionally, it serves as the basis for providing strengthening exercises for the lower limbs, which play a crucial role in supporting the recovery process of plantar fasciitis. Objective: This article aims to review how biomechanical gait analysis and strengthening exercises contribute to the recovery of plantar fasciitis and to identify rehabilitation mechanisms based on the latest scientific evidence. Methods: This narrative review analyzes literature from the past 10 years related to biomechanical gait analysis and strengthening exercises using the PICO framework (Population, Intervention, Comparison, Outcome). Literature searches were conducted using PubMed, Science Direct, Scopus, and PEDro. Results: From the search across four databases, several relevant journals were identified that indicated a relationship between biomechanical gait analysis and strengthening exercises for the recovery of plantar fasciitis. Conclusion: Biomechanical gait analysis and strengthening exercises can optimize the recovery of plantar fasciitis. Keywords: Biomechanical Gait Analysis; Plantar Fasciitis; Rehabilitation; Strengthening Exercises